OPTIMASI KETAHANAN WATERMARKING AUDIO DIGITAL MENGGUNAKAN ALGORITMA RSA DAN MSB - Rumahorbo, Benget; Perangin-angin, Resianta (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Copyright is a serious problem in the digital world, the process of sending and distributing digital media is so easy nowadays, copyright in the digital world is very detrimental to those who feel that their digital rights are copied and pasted or taken without the consent of the creator. Therefore we need a way where when a digital file can be identified as original as a product, one of the right ways is to use a watermark technique. But often this watermark process can be lost or cannot be extracted because the digital file has gone through a compression process, duplicate, or something else. So in this study, it will be tried to increase the durability of a watermark in digital audio as a solution for identifying copyrighted digital works. Where the watermark process will use the RSA and MSB algorithms to enter information into a digital audio file, later this information can be extracted to view copyright ownership information from the digital audio. And it is hoped that this watermarking is resistant to various digital audio processes such as compression, duplication, and editing carried out on the file. the information that is inserted into is maintained without compromising the quality of the digital audio.